Expanding tropical forest monitoring into Dry Forests: The DRYFLOR protocol for permanent plots. Issue 3 (13th July 2020) - Moonlight, Peter W.; Banda‐R, Karina; Phillips, Oliver L.; Dexter, Kyle G.; Pennington, R. Toby; Baker, Tim R.; C. de Lima, Haroldo; Fajardo, Laurie; González‐M., Roy; Linares‐Palomino, Reynaldo; Lloyd, Jon; Nascimento, Marcelo; et al.
Societal Impact Statement: Understanding of tropical forests has been revolutionized by monitoring in permanent plots. Data from global plot networks have transformed our knowledge of forests' diversity, function, contribution to global biogeochemical cycles, and sensitivity to climate change. Monitoring has thus far been concentrated in rain forests. Despite increasing appreciation of their threatened status, biodiversity, and importance to the global carbon cycle, monitoring in tropical dry forests is still in its infancy. We provide a protocol for permanent monitoring plots in tropical dry forests. Expanding monitoring into dry biomes is critical for overcoming the linked challenges of climate change, land use change, and the biodiversity crisis. Abstract : Understanding of tropical forests has been revolutionised by monitoring in permanent plots. Data from global plot networks have transformed our knowledge of forests' diversity, function, contribution to global biogeochemical cycles, and sensitivity to climate change. Monitoring has thus far been concentrated in rain forests. Despite increasing appreciation of their threatened status, biodiversity, and importance to the global carbon cycle, monitoring in tropical dry forests is still in its infancy. We provide a protocol for permanent monitoring plots in tropical dry forests. Expanding monitoring into dry biomes is critical for overcoming the linked challenges of climate change, land use change, and the biodiversity crisis.